(untitled) (Research, Society and Development, 2020)
In the Digital Age, the discussion that permeates the legal mechanisms that guarantee the intellectual property protection for software has been gaining prominence in the academic and business community. In this sense, this work aims to analyze the situation of the protection for software of the institutions that compose the Federal Network of Professional, Scientific and Technological Education (RFEPCT) filed at the National Institute of Industrial Property (INPI). This is a forecasting study, which was conducted in the database from INPI to gauging the requests of protection for software by institutions of RFEPCT in the period from 2009 to 2015. The results and discussions presented, was found that the institutions of RFEPCT maintain a growth trend in the number of protection for software in the INPI observed in the analyzed years, a fact that follows the national trend of protection for software also shows growth over the years.